Berberine and Its Main Metabolite Berberrubine Inhibit Platelet Activation Through Suppressing the Class I PI3Kβ/Rasa3/Rap1 Pathway - Wang, Can; Cheng, Yangyang; Zhang, Yuanhui; Jin, Hongtao; Zuo, Zengyan; Wang, Aiping; Huang, Jianmei; Jiang, Jiandong; Kong, Weijia (Frontiers in Pharmacology, 2021)
Background: Natural product berberine (BBR) was reported to inhibit platelet aggregation; however, the molecular mechanisms remain unclear. This study aims to investigate the effects and mechanisms of BBR to inhibit platelet activation and thrombus formation. Methods: Flow cytometry, immunofluorescence and western blot were used to determine the inhibitory effects and mechanisms of BBR and its main metabolite berberrubine (M2) on platelet activation in vitro and ex vivo. Purified integrin αIIbβ3, class I PI3K kit and molecular docking were used to identify the possible targets of BBR and M2. Carrageenan-induced mouse thrombosis model was used to evaluate the effects of BBR on thrombus formation in vivo. Results: In vitro, BBR and M2 significantly inhibited ADP-induced integrin αIIbβ3 activation, reduced the level of P-selectin on platelet membrane, and suppressed the binding of fibrinogen to platelets. In this process, BBR and M2 greatly suppressed the PI3K/Akt pathway, and inhibited Rasa3 membrane translocation and Rap1 activation. Furthermore, BBR and M2 selectively inhibited the class I PI3Kβ, perhaps through binding to its active site. The activities of BBR were stronger than M2. After oral administration, BBR significantly inhibited the PI3K/Akt pathway, Rap1 activation, and suppressed ADP-induced platelet activation and carrageenan-induced thrombosis in mice without prolonging bleeding time. Conclusions: We reveal for the first time the possible targets and mechanisms of BBR and M2 to inhibit platelet activation. Our research may support the future clinical application of BBR as an antiplatelet drug in the prevention or treatment of thrombotic diseases.